1981
DOI: 10.1128/jcm.14.2.201-205.1981
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acridine orange and Gram stains for detection of microorganisms in cerebrospinal fluid and other clinical specimens

Abstract: Acridine orange, a fluorochrome stain, is potentially superior to the Gram stain in the direct microscopic examination of clinical specimens because it gives striking differential staining between bacteria and background cells and debris. Its value in clinical laboratories was evaluated by testing 209 cerebrospinal fluids and 288 other body fluids, tissues, and exudates by both techniques. Smears were made in duplicate, fixed with methanol, stained, and examined without knowledge of the result of the companion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 10 publications
2
41
0
Order By: Relevance
“…Buffy coat smears stained with A 0 stain were more sensitive than those stained with Gram's stain ( p < 0.005). Dilution studies have shown the lower limits of sensitivity of A 0 to be lo4 colony forming units/ml and of Gram's stain to be lo5 colony forming units/ml (8,9). A 0 and Gram-stained buffy coat smears have had limited success in older children (1 0) and adults (1 l), as compared to neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Buffy coat smears stained with A 0 stain were more sensitive than those stained with Gram's stain ( p < 0.005). Dilution studies have shown the lower limits of sensitivity of A 0 to be lo4 colony forming units/ml and of Gram's stain to be lo5 colony forming units/ml (8,9). A 0 and Gram-stained buffy coat smears have had limited success in older children (1 0) and adults (1 l), as compared to neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a more sensitive means for detecting those organisms that are present at a low level or that are less visible after Gram staining has been recognized. For example, acridine orange, Wayson, and other staining procedures have shown enhanced sensitivity for observing organisms (1,3,7). However, these stains do not increase the number of organisms on the slide.…”
Section: Discussionmentioning
confidence: 99%
“…After drying overnight, the slides were stained by gently placing three drops of 0.01% acridine orange solution (in pH 3.5 acetate buffer) and then gently rinsed with filtersterilized distilled water and returned to the microscope slide box to dry in the dark (Lauer et al, 1981;Siering and Ghiorse, 1997).…”
Section: -3: Environmental Sinter Collection Preparation and Examinmentioning
confidence: 99%